2007
DOI: 10.1021/ac070235u
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Fluorescence Signaling DNA Enzymes in Sol−Gel-Derived Materials for Metal Ion Sensing

Abstract: Three fluorescence signaling DNA enzymes (deoxyribozymes or DNAzymes) were successfully immobilized within a series of sol-gel-derived matrixes and used for sensing of various metal ions. The DNAzymes are designed such that binding of appropriate metal ions induces the formation of a catalytic site that cleaves a ribonucleotide linkage within a DNA substrate. A fluorophore (fluorescein) and a quencher (DABCYL, [4-(4-dimethylaminophenylazo)benzoic acid]) were placed on the two deoxythymidines flanking the ribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 56 publications
0
53
0
Order By: Relevance
“…We term this type of DNAzyme "RNA-cleaving fluorogenic DNAzyme", or simply "RFD". Over the past decade, we have isolated many RFDs and examined their catalytic and signaling properties [38,39,[67][68][69][81][82][83][84][85][86][87][88][89][90]. More recently, we began to develop RFDs that that can be activated in the presence of a specific bacterium, such as Escherichia coli and Clostridium difficile [72,80,82,[91][92][93][94][95][96].…”
Section: In Vitro Selection Of Rna-cleaving Dnazymes For Bacterial Dementioning
confidence: 99%
“…We term this type of DNAzyme "RNA-cleaving fluorogenic DNAzyme", or simply "RFD". Over the past decade, we have isolated many RFDs and examined their catalytic and signaling properties [38,39,[67][68][69][81][82][83][84][85][86][87][88][89][90]. More recently, we began to develop RFDs that that can be activated in the presence of a specific bacterium, such as Escherichia coli and Clostridium difficile [72,80,82,[91][92][93][94][95][96].…”
Section: In Vitro Selection Of Rna-cleaving Dnazymes For Bacterial Dementioning
confidence: 99%
“…Being a polyanion, the diffusion of entrapped DNA may 7 be reduced by increasing the DNA length, gel percentage, or by using cationic monomers to form the gel. 65 The diffusion may be further reduced by linking DNA to large proteins and microparticles. Copolymerization of acrydite-modified DNA into polyacrylamide.…”
Section: Conjugate Chemistrymentioning
confidence: 99%
“…The authors further showed the use of such entrapped aptamer sensors to perform high throughput screening for enzyme inhibitors and for metal ion detection. 65,102 Nielsen et al employed an aptamer sensor design first reported by the Tan group ( Figure 8C). 103 In this case, the sensor is composed of only a single DNA strand which contained a fluorophore, a quencher, the ATP aptamer sequence and a polymer spacer.…”
Section: Dna Sensors Entrapped In Gelsmentioning
confidence: 99%
“…By placing a fluorophore-quencher pair directly on the RNA cleavage substrate from the outset of selection, more effective signaling deoxyribozymes have been identified [116]. Efforts have been made to entrap fluorescently signaling deoxyribozymes in sol-gel matrices, which may have certain benefits over solutionphase assays [117], and an electrochemical Pb 2+ sensor based on metal-dependent RNA cleavage has been developed [118]. The fluorophore and quencher components of the general system have also been replaced with gold nanoparticles, which change color upon cleavage-induced disassembly, allowing simple colorimetric detection of metal ions [110,119,120].…”
Section: Regulated Rna-cleaving Deoxyribozymes As Sensorsmentioning
confidence: 99%